Spatial Distribution of Birds in Coban Trisula, Bromo Tengger Semeru National Park - Iqbal, Kemal; Gama, Zulfaidah Penata; Yanuwiadi, Bagyo (Proceeding International Conference on Global Resource Conservation, 2015)
Bromo Tengger Semeru National Park has vegetation that allows the availability of suitable habitat for various species of birds. Species of birds that can be found in Coban Trisula are very diverse. The purpose of this research was to determine the spatial distribution patterns of birds in Coban Trisula area. This study used point count method. The observation was conducted in February to April 2015. Species data were calculated and presented in the form of tables and figures. The spatial distribution of birds was determined by using an index of dispersion. The results of the study showed that 43 species of birds consists of 6 Order and 17 Family. The spatial distribution result showed that the majority of spatial distribution pattern were in aggregation patterns. In theory, aggregation patterns in species of birds can be concluded that they are sharing foraging area (sharing resources), safe, easy to meet between males and females as well as their natural character. Â Keywords: birds; Coban Trisula; spatial distribution